2020
DOI: 10.1155/2020/9794823
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile Enteritis Induced Anastomotic Rupture: A Case Report and Literature Review

Abstract: Background. A 76-year-old male patient who suffered small bowel anastomotic dehiscence believed to be a complication provoked by Clostridioides difficile enteritis. Case Presentation. The patient was a 76-year-old male who underwent small bowel resection with primary anastomosis for a small bowel obstruction. On postoperative day #7, he rapidly decompensated and upon return to the operating room was found to have complete anastomotic dehiscence with copious enteric spillage. The presentation appeared as if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A Japanese group also reported seven patients (3.8 per cent) with anastomosis leakage from a cohort of 185 colorectal surgery cases and indicated that CDI was significantly associated with leakage ( P = 0.001). Finally, few case reports of anastomosis rupture related to CDI have been published 13 , 16 . Although the number of cases of anastomosis leakage after ileostomy closure is very small, the current findings indicate a higher rate of leakage in CDI-positive patients versus negative cases (8.7 per cent versus 1.4 per cent, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese group also reported seven patients (3.8 per cent) with anastomosis leakage from a cohort of 185 colorectal surgery cases and indicated that CDI was significantly associated with leakage ( P = 0.001). Finally, few case reports of anastomosis rupture related to CDI have been published 13 , 16 . Although the number of cases of anastomosis leakage after ileostomy closure is very small, the current findings indicate a higher rate of leakage in CDI-positive patients versus negative cases (8.7 per cent versus 1.4 per cent, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Veterinary studies were excluded, as were basic science studies and articles focusing on pediatric patients (age <18 years). Per our selection strategy, 77 reported cases were identified in 49 publications and our results are presented in Table 1 [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%